AKUNTABILITAS PENGELOLAAN DANA DESA (STUDI FENOMENOLOGI PADA DESA LAMUNDE KECAMATAN WATUBANGGA KABUPATEN KOLAKA): AKUNTABILITAS PENGELOLAAN DANA DESA (STUDI FENOMENOLOGI PADA DESA LAMUNDE KECAMATAN WATUBANGGA KABUPATEN KOLAKA) - Irmayanti Irmayanti; Syamsuri Rahim; Sumarni Sumarni (Jurnal Ilmiah Ekonomi Dan Bisnis, 2023)
concerning Village Financial Management Article 43-62. Meanwhile, the implementation This study aims to determine how the accountability of Village Fund management which includes planning, implementation, administration, reporting and accountability in Lamundre Village, Watubangga District, Kolak Regency. The research method used is a qualitative phenomenological research method . The data analysis technique used is a qualitative descriptive analysis technique using the Miles and Huberman model. Activities in data analysis are: data reduction, display, and conclusion drawing/verification. Sources of data are primary data and secondary data. Data collection techniques were carried out by observation, interviews, and documentation.The results of the study show that: (1) Planning has implemented the principles of participation and transparency, however in implementing the principles of participation and transparency still need to be improved in order to obtain quality planning results. (2) Implementation , at this stage the Village Government has implemented the principle of accountability related to receipts and expenditures in accordance with with Permendagri No. 20 of of the principles of transparency and accountability by the Activity Implementation Team (AIT) not yet fully done . (3) Administration at this stage in general has implemented the principle of accountability and is in accordance with the administration as stated in Permendagri Number 20 of 2018 concerning the management of Village Finance in articles 63-64. (4) Reporting and accountability in the reporting stage of the village government has applied the principle of reporting accountability in accordance with Permendagri No. 20 of 2018 concerning Village Financial Management article 68. Meanwhile, Village Fund Accountability in Lamundre Village, Watubangga District, Kolaka Regency is integrated with APBDes accountability. This is in accordance with Permendagri Number 20 of 2018 articles 70-71 regarding village financial reporting and accountability. However, horizontal accountability is still considered insufficient to describe the application of the principle of accountability to the community, as well as increasing the capacity of the village apparatus in order to create a perfect application of the principle of accountability in the management of Village Funds in Lamundre Village. Keywords: accountability, village fund management